The “Ideal” TH Model Framework to Promote Knowledge Talent : a Malaysian Case - Nadia Mohd Salleh, Masrina; Tasnim, Rahayu; ., . (International Journal of Engineering and Technology, 2018)
The Talent is viewed as a competitive issue. Meanwhile, Knowledge Talent is indeed required for shaping an innovative ecosystem sphere. Malaysia is still fighting the “Knowledge Talent” war due to the rising talent and skill gap between available graduates and industries’ demands.  Profound collaboration between the Government, University and Industry known as Triple Helix (TH) model has been highlighted as the main driver to fill this gap. Providing an exploration of the fundamental conditions and contextual sensitivity that hinder university-industry linkages, this paper suggest the ideal TH model framework to fill the gap and provide a solid basis by considering institutionalism perspective in the Malaysia context. The evolutionary perspective stipulates better understanding of overlay in communication and gap between the Government, University and Industry to reshape the Knowledge Talent pool systems to fill the gap in contributing to the transition of a hybrid TH culture-taking root.
Keywords: Knowledge Talent; Innovation; Talent & Innovation; University-Industry Linkages; Triple Helix in Malaysia; Scientific and Technical publications